(untitled) (Proceedings of International Conference on Modern Science and Scientific Studies, 2023)
Currently, the relationship between parents and children is changing both quantitatively and qualitatively. This has an impact on the upbringing of children and is becoming increasingly important in shaping their social roles. The article highlights the influence of family relations and the role of parents in the acquisition of gender roles by the child.